A low-cost computerised electronic stethoscope with pre-diagnosis and easy transmission features. (2017) - Daou, Roy Abi Zeid; Sadek, Katy; Karim, Michel Bou; Makhlouf, Paul
Digital stethoscopes already exist in the market. However, their prices are not always affordable by many medical doctors and patients and most of them do not embed the telemedicine and/or the pre-diagnostic features. Thus, the proposed system presents a novel approach to record, save, process, analyse, diagnose and send data coming from the stethoscope to the healthcare professional that is not present near the patient. This low-cost system aims also to give a pre-diagnosis regarding his heart and/or his chest behaviours. The pre-diagnostic and the data processing are executed using LabView software. Some of the system features are to save the records of the patient and compare them over time, transmit the saved signal to the doctor's email or uploading them on the web, show the placement of the stethoscope sensors depending on the required reading, etc. Good results were obtained when comparing the exact values (using the conventional stethoscope) and the transmitted ones (file generated when recording the heart/lung signals). Added to that, the basic diagnoses given by the software were not far from the real ones. 60 persons were tested by three medical doctors and signals generated from the systems were almost the same as the exact signals. Thus, the proposed system could be bought by any patient or healthcare professional for its accurate results, easy handling, portability and telemedicine feature.